Structural diversity of native major ampullate, minor ampullate, cylindriform, and flagelliform silk proteins in solution - Greving, I; Terry, AE; Holland, C; Boulet-Audet, M; Grillo, I; Vollrath, F; Dicko, C (American Chemical Society, 2020)
The foundations of silk spinning, the structure, storage, and activation of silk proteins, remain highly debated. By combining solution small-angle neutron and X-ray scattering (SANS and SAXS) alongside circular dichroism (CD), we reveal a shape anisotropy of the four principal native spider silk feedstocks from Nephila edulis. We show that these proteins behave in solution like elongated semiflexible polymers with locally rigid sections. We demonstrated that minor ampullate and cylindriform proteins adopt a monomeric conformation, while major ampullate and flagelliform proteins have a preference for dimerization. From an evolutionary perspective, we propose that such dimerization arose to help the processing of disordered silk proteins. Collectively, our results provide insights into the molecular-scale processing of silk, uncovering a degree of evolutionary convergence in protein structures and chemistry that supports the macroscale micellar/pseudo liquid crystalline spinning mechanisms proposed by the community.